Bank Capital Regulation with an Opportunistic Rating Agency - Matthias Efing (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper models the strategic interaction between a rating agency, a bank and a bank regulator who lacks information about bank asset risk. The regulator can either (1) make bank capital requirements contingent on credit ratings; or (2) set rating-independent capital requirements. Truthful ratings provide efficiency gains because they allow the regulator to constrain high risk bank investment without simultaneously reducing overall investment volume. However, if collusion between the rating agency and the bank corrupts rating quality, rating-independent regulation enhances welfare. The welfare benefits are largest if regulators maintain rating-contingent capital requirements and discipline rating agencies.
Keywords: D82; G21; G24; G28; 330; bank regulation; Lucas critique; collusion; ratings inflation; risk-shifting